MENINGKATKAN PRESTASI BELAJAR IPS MENGGUNAKAN METODE MIND MAPPING PADA SISWA KELAS V SD N NGRAHO 4 KEDUNGTUBAN BLORA - Sutrisno Sutrisno (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2015)
This research aims to improve learning achievement IPS Method Using Mind Mapping In Grade V SD N Ngraho 4 Kedungtuban Blora, Central Java Year 2014/2015. Thistype of research is classroom action research (PTK) with the research subjects are students ofclass V of 20 students and its object is the implementation of learning to improve learningachievement IPS by applying the method Mind Mapping on the material Proclamation ofIndonesian Independence. Data collection techniques used are observation, interviews, tests,questionnaires, and documentation. Techniques of data analysis in this research is to calculatethe average and percentage. The study concluded that social studies learning by using MindMapping can improve student achievement than the average achievement grade before theaction of 53.45 with 30.00% completeness increase in cycle 1 with average achievementgrade of 62.06 with thoroughness 60.00% and increased again in the second cycle with anaverage grade of 69.55 accomplishments with the thoroughness of 80.00% in the secondcycle, so that it can be concluded the average learning achievement increased by 17.38%.Feasibility study results of questionnaire responses learn first cycle of 70.87% with highqualifications be 87.08% with a very high qualification in the second cycle so that theresponse of learning has increased by 88.25%.